Unified Complex Systems Theory (UCST): Resolving Materialist Dilemmas Through Dualist Ontology and Active Force - Cui, Weicheng; Li, Rong; Pan, Lingli (European Journal of Applied Sciences, 2025)
The fragmentation of complex system theories, contradictions in foundational physics, and the inability of materialist science to explain the consciousness phenomena of the living agency in a complex system have long hindered interdisciplinary progress. This study presents the Unified Complex Systems Theory (UCST), a novel framework addressing these gaps by generalizing classical mechanics, establishing a dualist mind-body ontology, and introducing active force into mechanics. Rooted in 33 core axioms, UCST clarifies ambiguous fundamental concepts (e.g., universe/world, mass, vacuum), axioms and unifies micro-macro and non-living-living systems under a single dynamical equation integrating passive (physical) and active (mind-derived) forces. We demonstrate UCST’s ability to resolve intractable materialist problems—including the mind-body dilemma, action-at-a-distance paradox, and altruism’s ethical foundation—and validate its predictions via testable experiments (e.g., active force measurement, aether detection). By bridging science, ethics, and spirituality, UCST advances a postmaterialist paradigm that expands the boundaries of scientific inquiry.